Analisis Kinerja Keuangan Perusahaan dengan MetodeEconomic Value Added (EVA) dan Market Value Added (MVA) pada PT. Astra International Tbk. Tahun 2008-2012 - Dhito Dharmesta; Harlen dro (Jurnal Ilmiah Mahasiswa FEB, 2012)
Abstract :Rapid economic growth increasingly tightening competition among business people as well as the opportunity to earn greater profits. Good performance management is needed in order to achieve the company's goals and prosperity donors can be improved. This is a descriptive quantitative research that aims to determine the company's financial performance analysis tools Economic Value Added (EVA) and Market Value Added (MVA) at PT. Astra International Tbk. The data used in this study is a secondary data obtained from the IDX Corner Faculty of Economics and Business Universitas Brawijaya, Malang. The results showed that over a span of five years of research, namely the year 2008-2012, the company produced positive EVA value. It means that management has succeeded in creating added value for its investors because it has managed to meet the expectations of its investors to earn returns that exceed the issued capital. While the value of the resulting MVA also positive, meaning that the market appreciates that capital exceeds diivestasikan company so that management has been able to increase the wealth of its shareholders. The higher the value the better the MVA means that the performance of management in maximizing the wealth of its shareholders. Keywords : Financial Performance, Economic Value Added (EVA), Market Value Added (MVA)